2015
DOI: 10.1523/jneurosci.3375-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and Tectal "Driver-Like" Inputs Converge in the Shell of the Mouse Dorsal Lateral Geniculate Nucleus

Abstract: The dorsal lateral geniculate nucleus (dLGN) is a model system for understanding thalamic organization and the classification of inputs as "drivers" or "modulators." Retinogeniculate terminals provide the primary excitatory drive for the relay of information to visual cortex (V1), while nonretinal inputs act in concert to modulate the gain of retinogeniculate signal transmission. How do inputs from the superior colliculus, a visuomotor structure, fit into this schema? Using a variety of anatomical, optogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
129
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 66 publications
13
129
0
Order By: Relevance
“…Within sham animals, the distribution of VGLUT2 immunoreactivity occurred in large clusters of variable size, likely composed of multiple axon terminals as they synapse on proximal dendrites of relay neurons. These axon terminal clusters appeared evenly distributed throughout dLGN, a finding consistent with reports on the normal ultrastructure of retinogeniculate synapses upon relay neurons within dLGN (Bickford et al, 2015, 2010; Guido, 2008; Hammer et al, 2015, 2014; Morgan et al, 2016). Comparison of VGLUT2 immunoreactivity in mTBI animals 4 days post-injury to sham demonstrated the persistence of clusters (Figure 1B & D), however, the clusters in dLGN were more widely separated from each other, suggestive of axon terminal loss.…”
Section: Resultssupporting
confidence: 90%
“…Within sham animals, the distribution of VGLUT2 immunoreactivity occurred in large clusters of variable size, likely composed of multiple axon terminals as they synapse on proximal dendrites of relay neurons. These axon terminal clusters appeared evenly distributed throughout dLGN, a finding consistent with reports on the normal ultrastructure of retinogeniculate synapses upon relay neurons within dLGN (Bickford et al, 2015, 2010; Guido, 2008; Hammer et al, 2015, 2014; Morgan et al, 2016). Comparison of VGLUT2 immunoreactivity in mTBI animals 4 days post-injury to sham demonstrated the persistence of clusters (Figure 1B & D), however, the clusters in dLGN were more widely separated from each other, suggestive of axon terminal loss.…”
Section: Resultssupporting
confidence: 90%
“…These neurons respond best to slowly moving stimuli and project to the pulvinar, whereas the horizontal neurons express GABA and project to the lateral geniculate nucleus, as well as the parabigeminal nucleus (Gale & Murphy 2014). Recent optogenetic studies show that there are also excitatory projections to the dorsal lateral geniculate nucleus (Bickford et al 2015). These new results, together with the known properties of retinal afferents and their recent molecular identification (Bowling & Michael 1980, Huberman et al 2009, Sachs & Schneider 1984, Tamamaki et al 1995), suggest the visuosensory layers process and relay visual information related to motion and orienting (Hall & Colby 2016, White et al 2009).…”
Section: Basic Anatomy Of the Superior Colliculus A Layered Strucmentioning
confidence: 99%
“…Just as classes of relay cells are differentially distributed in cat and primate dLGN (Sherman, 1985; Nassi & Callaway, 2009), they are uniquely distributed in mouse dLGN: W-like cells occupy the dorsolateral shell of mouse dLGN and X- and Y-like cells occupy the ventromedial dLGN core (Krahe et al, 2011). While all three classes of TC relay cells project axons to visual cortex, recent evidence has demonstrated that regionally restricted cell types participate in functionally distinct parallel visual pathways in mice (Cruz-Martín et al, 2014; Bickford et al, 2015). …”
Section: Cytoarchitectural Organization Of Retinorecipient Thalamic Nmentioning
confidence: 99%
“…These inputs arise from the ipsilateral superior colliculus (SC) and terminate onto W-like TC relay cells in the dorsolateral shell of dLGN (Harting et al, 1991 a ; Bickford et al, 2015). Circuit tracing experiments indicate these excitatory tectogeniculate connections contribute to the processing and transmission of direction-selective visual information (Bickford et al, 2015). …”
Section: Afferent Projections Of Retinorecipient Thalamic Nucleimentioning
confidence: 99%